Biomechanical determinants of change of direction performance: a systematic review - Singh, U.; Leicht, A. S.; Connor, J. D.; Brice, S. M.; Alves, A.; Doma, K. (Sports Medicine, 2025)
Background: The ability to change direction rapidly is crucial for enhancing performance in multidirectional sports. Evidence suggests that several biomechanical variables are associated with faster change of direction (COD) completion times. However, while it is understood that biomechanical factors influence COD performance, the evidence remains unclear because of the diverse range of biomechanical factors, inconsistent findings and potential influences from various moderating factors (e.g. sex, training experience). Objective: The primary aim of this systematic review was to identify the biomechanical determinants of COD performance while the secondary aim was to examine the impact of moderating factors on the determinants. The findings of this review could assist practitioners in designing effective training and coaching strategies to improve COD performance. Methods: A systematic literature search was conducted across the electronic databases of Scopus, PubMed, Web of Science, CINAHL, and SPORTDiscus. Studies were considered eligible if they involved healthy participants, considered biomechanical determinants of COD performance via correlational analyses and reported COD performance (i.e. time to completion). The quality of the study was assessed via the Kmet scale while study findings were collated. Results: A total of 13 studies met the inclusion criteria and analysed 45-180° COD tasks involving 374 participants. Kmet scores ranged from 73 to 96%, indicating good-to-excellent methodological quality of studies. Several biomechanical variables were identified as contributors to quicker COD completion times, including shorter ground contact time, higher approach and exit velocities, increased braking and propulsive forces, greater trunk inclination angle, lower centre-of-mass height, and increased moments and power at the hip, knee and ankle. With respect to moderating factors, included studies utilised various COD tasks (45-180°), examined mostly male participants (79.4%) with inconsistent reporting of playing/training experience and all consisted of a pre-planned COD task only. Conclusions: Our findings identified several key biomechanical variables that were important determinants of faster COD performance. However, the impact of moderating factors on COD performance was minimally examined in prior studies and requires further investigation. Recommendations are provided in this paper focussing on biomechanical contributors (e.g. ground contact time, approach velocity, braking forces), which may assist coaches with relevant training modalities to enhance COD performance.